Educational effectiveness of cognitive and metacognitive strategies on educational self-destructive behaviors and negative self-evaluation thinking in Arabic lessons - Ali Nourihamid Altome; Mohammad hassani; Masoumeh Talebi (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is the educational effectiveness of cognitive and metacognitive strategies on educational self-defeating behaviors and negative self-evaluation thinking in Arabic lessons. This research is an applicable in terms of purpose, and quasi-experimental research with a pre-test-post-test design with a reference group. The statistical population of the research includes the middle school students of the holy city of Karbala, 105 of whom were selected by multi-stage cluster random sampling, and randomly divided into three groups of 35 (a control group of 35 and two experimental groups of 35 people). Data collection was done based on the standard questionnaire of educational self-defeating behaviors of Jones and Rudalt (1982) and negative self-evaluation thinking of Jaj et al, (2003). The face and content validity of the questionnaire was approved by the professors and experts of educational sciences and was confirmed through factor analysis, and the reliability of the questionnaire was obtained based on Cronbach's alpha coefficient of educational self-defeating behaviors of 0.88 and negative self-evaluation thinking of 0.86. The analysis of the information obtained from the tests was done through SPSS22 software in two descriptive sections including mean, standard deviation, skewness, and kurtosis; and inferential (covariance analysis). The results of the research showed that teaching cognitive and metacognitive strategies has a positive and significant effect on reducing educational self-defeating behaviors and negative self-evaluation thinking of students. It is suggested to teach cognitive and metacognitive strategies according to students in a practical way in schools, workshops and training courses. Extended abstract Introduction Researchers tested many human needs and motivations and thus new theories were proposed, one of whom is the theory of documents. According to this theory, when faced with others, people try to attribute failure to external factors such as luck and task difficulty; and success to internal factors such as talent and ability. After that, two researchers named Berglas and Jones (1987) noticed that sometimes people, instead of justifying their performance after receiving feedback, use strategies in advance to justify the next possible failure. They called these strategies educational self-defeating behaviors, because their use leads to weakening performance (Jalili, 2014). Educational self-destructive behaviors are a group of preconditions that people provide, in the hope that they will replace factors that may doubt their competence in the future. Self-destructive behavior indicates a situation in which, although a person is trying to achieve a goal, he chooses ways that are associated with many unfortunate events and prevent him to reach the goal or make it difficult (Ajdarbin et al., 2023). Therefore, self-destructive behaviors in students lead to failure and self-harm, and ultimately, it will be accompanied by a drop in self-esteem, a decrease in psychological well-being, and as a result, with negative consequences such as academic failure (Ajdarbin et al, 2023). In the educational system, unfortunately, the Arabic language teaching methods were very unprincipled and relied on the teaching of strict and complex rules of morphology and syntax that had little connection with the needs of the day and information related to various aspects of life. Recent research findings also emphasize that the level of Arabic language education in schools is below the desired level (Rasoli, 2005). Besides, the process of teaching Arabic language has neglected the psychological issues of language teaching, cognitive and metacognitive elements such as motivation, excitement, intelligence, etc., and only sufficed to present texts for understanding and dialogue for a transient an deficient interaction (Azarshab & Homayuni 2015), as a result, we see educational self-defeating behaviors under the influence of self-evaluation thoughts, not negative, in learning Arabic among students. Based on this, the main problem of the current research is: to what extent is the educational effectiveness of cognitive and metacognitive strategies and educational self-defeating behaviors and negative self-evaluation thinking in Arabic lessons among students? Theoretical Framework Cognitive and metacognitive strategies A strategy is a general plan or a set of operations planned to achieve a certain goal. It is said that the most important learning strategies can be mentioned are cognitive and metacognitive strategies. Researchers have classified students' learning activities in the form of three cognitive, emotional, and metacognitive activities. Cognitive strategies are learning tools that help people prepare new information to combine with previously learned information and store it in long-term memory. These strategies include the strategies of repetition and review, expansion and stretch of meaning, and organization (Saif, 2022). Educational self-defeating behaviors Researchers have defined educational self-destructive behaviors as the process of having a lot of stress in facing the challenges ahead in school and not using the skills that help the student to overcome these conditions. These behaviors mainly have destructive effects on the learner's mental health. People with self-destructive behaviors will usually get negative results from their performance (Moradi & Mohammadi, 2020). Negative self-evaluation thinking Studies have shown that behaviors such as procrastination and self-handicapping can be the result of negative thoughts and cognitions such as negative self-evaluation (Rad et al, 2023). Studies show that there is a positive and significant relationship between educational self-destructive behaviors (academic self-handicapping) and negative and pessimistic self-evaluative thoughts. Negative self-evaluative belief is a multifaceted concept and includes knowledge (beliefs), processes and strategies that negatively evaluate, monitor or control cognition (MacBeth et al, 2019). Ali Bakshi & Maghanlou (2023) investigated the relationship between academic self-efficacy and negative self-evaluative thinking among female high school students. The results showed that there is a significant negative relationship between academic self-efficacy and educational self-defeating behaviors among female high school students. Educational self-destructive behaviors have a negative and significant effect on academic self-efficacy with a rate of 0.24. Discussion and conclusion: In order to improve the self-employment level of secondary school students, attention should be paid to their educational self-destructive behaviors. Idris et al, (2022) investigated the use of cognitive and metacognitive strategies in foreign language learning. The results showed that cognitive and metacognitive strategies have a positive and significant effect on learning a foreign language (French). Research methodology This research is an applicable in terms of purpose, and quasi-experimental research with a pre-test-post-test design with a reference group. The statistical population of the research includes the middle school students of the holy city of Karbala, 105 of whom were selected by multi-stage cluster random sampling and randomly divided into three groups of 35 people (a control group of 35 people and two experimental groups of 35 people). Data collection was based on the standard questionnaire of educational self-defeating behaviors of Jones and Rudalt (1982) and negative self-evaluation thinking of Jaj et al. (2003). The face and content validity of the questionnaire was approved by professors and experts in educational sciences and was confirmed through confirmatory factor analysis. The reliability of the questionnaire was 0.88 based on Cronbach's alpha coefficient of self-destructive educational behaviors and 0.86 negative self-evaluation thinking. Research findings The analysis of the information obtained from the tests was done through SPSS22 software in two descriptive sections including mean, standard deviation, skewness, and kurtosis; and inferential (covariance analysis). The results of the research showed that teaching cognitive and metacognitive strategies has a positive and significant effect on reducing educational self-defeating behaviors and negative self-evaluation thinking of students. It is suggested to teach cognitive and metacognitive strategies according to students in a practical way in schools, workshops and training courses. Conclusion The current research was conducted with the aim of educational effectiveness of cognitive and metacognitive strategies on educational self-destructive behaviors and negative self-evaluation thinking in Arabic lessons. The findings are in line with the results of Ajdarbin et al, (2023), Ali Bakshi & Maghanlou (2023), Idris et al, (2022), Shad & Razmkhah (2021), Iranmanesh et al, (2020), Rashidzadeh et al, (2019), Alanazi & Alenizi (2016), Lonie & Desai (2015), and Nair et al, (2014). Iranmanesh et al, (2020) showed that teaching cognitive and metacognitive strategies is effective in changing the level of educational self-defeating behaviors and negative self-evaluation thinking. In line with the obtained results, it is suggested that considering the effect of teaching cognitive-metacognitive strategies in reducing academic self-defeating behaviors and negative self-evaluative thinking, the results of the researches conducted in this field should be used practically in other schools and educational centers, and cognitive and metacognitive strategies should be taught according to the students in schools, educational workshops and training courses.